2018
DOI: 10.1101/359950
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thyroid hormone signaling specifies cone subtypes in human retinal organoids

Abstract: The mechanisms underlying the specification of diverse neuronal subtypes within the human nervous system are largely unknown. The blue (shortwavelength/S), green (medium-wavelength/M) and red (long-wavelength/L) cone photoreceptors of the human retina enable high-acuity daytime vision and trichromatic color perception. Cone subtypes are specified in a poorly understood two-step process, with a first decision between S and L/M fates, followed by a decision between L and M fates. To determine the mechanism contr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
82
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(91 citation statements)
references
References 52 publications
9
82
0
Order By: Relevance
“…Therefore, the ratio of cones to rods in our retinal organoids is higher than the ratio found in the macula and lower than the ratio in the fovea. The regulator for cone commitment is still elusive (57), although thyroid hormone signaling directs cone subtypes in mice and human retina (16,58). In our floating culture, abundant cone photoreceptors spontaneously differentiate from VSX2 + epithelium, consistent with the default cone commitment hypothesis in the retina (57).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Therefore, the ratio of cones to rods in our retinal organoids is higher than the ratio found in the macula and lower than the ratio in the fovea. The regulator for cone commitment is still elusive (57), although thyroid hormone signaling directs cone subtypes in mice and human retina (16,58). In our floating culture, abundant cone photoreceptors spontaneously differentiate from VSX2 + epithelium, consistent with the default cone commitment hypothesis in the retina (57).…”
Section: Discussionsupporting
confidence: 73%
“…Although retinal organoids with differentiated cone and rod photoreceptors were previously reported by us and others (7,8,11,(13)(14)(15)(16)(17), the ratio of cones to rods has not been rigorously determined using scRNA-seq until the current study. Based on immunostaining, Li et al (13) found seven rod-rich and six conerich retinal organoids out of 14 retinal organoids, but the ratio of cones to rods was not quantified.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Photoreceptor transplantation studies focusing on cones can now be tested in the genetic model of achromatopsia, taking advantage of the cone-silent state and relatively stable architecture of the macula in these NHPs (9). Cone replacement has suffered from challenges in the production of cone photoreceptors in vitro from human iPSC-derived retinal organoids, although some strategies have been reported to bias cells to adopt this fate (126,127). There is now renewed interest in investigating human cell transplantation to the retina (128), as advances in the past decade using mouse models appear to be in part secondary to material transfer between transplanted cells and endogenous cells (129,130).…”
Section: Therapy Development Involving Nonhuman Primates In Vivomentioning
confidence: 99%